2001
DOI: 10.1007/s005950170116
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Liver Carcinomas with Sarcomatous Features: Analysis of Four Cases

Abstract: We recently examined the clinicopathological and immunohistochemical features of four cases of primary hepatic carcinoma with sarcomatoid elements. Three of the four patients had associated ordinary hepatocellular carcinoma (HCC) and one had a sarcomatoid carcinoma with no apparent elements of HCC. The presenting symptoms were high fever and hypochondralgia in three patients, and right hypochondralgia without a high fever in one. The preoperative diagnoses were liver abscess in two patients, HCC in one, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 8 publications
4
18
0
5
Order By: Relevance
“…In addition, the immunohistochemical study for cytokeratin, epithelial membrane antigen, hepatocyte and vimentin is helpful in the pathological diagnosis [6]. Generally, components of sarcomatoid lesions are positive for both cytokeratin (epithelial marker) and vimentin (mesenchymal marker) [1, 2, 10]. The tumor in the present case was diffusely positive for vimentin and cytokeratin 7, and focally positive for hepatocytes, which is consistent with sarcomatoid HCC.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, the immunohistochemical study for cytokeratin, epithelial membrane antigen, hepatocyte and vimentin is helpful in the pathological diagnosis [6]. Generally, components of sarcomatoid lesions are positive for both cytokeratin (epithelial marker) and vimentin (mesenchymal marker) [1, 2, 10]. The tumor in the present case was diffusely positive for vimentin and cytokeratin 7, and focally positive for hepatocytes, which is consistent with sarcomatoid HCC.…”
Section: Discussionsupporting
confidence: 62%
“…When compared with typical HCC, the prognosis of sarcomatoid HCC was unfavorable due to widespread metastasis [1, 4, 9, 10]. Hwang et al [11] reported that the 3-year survival rates for sarcomatoid HCC after liver resection and liver transplantation were 18.2 and 37.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in previous studies, adjacent organ invasion and lymph node metastasis were relatively less frequent in ordinary HCC than in HCC with SC. 3,15,16 We felt this highly invasive behavior might be attributed to the sarcomatous component in HCC with SC. Since HCC with SC was highly aggressive, it had a higher tendency for advanced stage tumor than ordinary HCC, and was thus the reason why TNM staging was different between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, SC in HCC patients who had not previously undergone anticancer therapy has been also reported. 3,9,10 Clinically, the presence of SC in HCC is thought to be associated with more aggressive tumor biology, higher rates of recurrence, more frequent metastasis, and poorer survival. [5][6][7] Even in patients with curative resection, the possibility of local recurrence or distant metastasis is extremely high.…”
mentioning
confidence: 99%
See 1 more Smart Citation